PENGARUH BOOK TAX GAP DAN ARUS KAS TERHADAP PERSISTENSI LABA PADA PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Rangkuti, Anggita Sari; Rialdy, Novien (Gapenas Publisher, 2025)
This study aims to examine and analyze the effect of cash flow and the difference between accounting profit and fiscal profit on earnings persistence in food and beverage companies listed on the Indonesia Stock Exchange (IDX) for the 2016 - 2019 period. The population used in this study were 26 food companies. and beverages listed on the Indonesia Stock Exchange, while the samples taken were 9 food and beverage companies using purposive sampling. The data analysis technique in this research is using Descriptive Statistical Analysis, Simple Linear Regression analysis, classical assumption test, hypothesis testing, and Coefficient of Determination with a significance level of 5%. The data processing in this study used the SPSS (Statistics Pakcage for the Social Sciences) software program for Windows version 23.00. The results of this study indicate that cash flow has no significant effect on earnings persistence of -0.415 with a significance of 0.681. The difference between Accounting Profit and Fiscal Profit has a significant effect on Earning Persistence of 11.510 with a significance of 0.000. Cash flow and the difference between accounting profit and fiscal profit together have a significant effect on earnings persistence of 66.978 with a significance of 0.000